Polio : an American story - Oshinsky, David M., 1944- (Oxford University Press, 2005)
[This book] tells the ... story of the polio terror and of the intense effort to find a cure, from the March of Dimes to the discovery of the Salk and Sabin vaccines--and beyond.-Dust jacket.